2013
DOI: 10.1016/j.conb.2012.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Consciousness supporting networks

Abstract: This article appeared in a journal published by Elsevier. The attached copy is furnished to the author for internal non-commercial research and education use, including for instruction at the authors institution and sharing with colleagues.Other uses, including reproduction and distribution, or selling or licensing copies, or posting to personal, institutional or third party websites are prohibited. Author's personal copy In most cases authors Consciousness supporting networksAthena Demertzi, Andrea Soddu and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
124
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 173 publications
(141 citation statements)
references
References 47 publications
(54 reference statements)
14
124
0
3
Order By: Relevance
“…3); this finding is also consistent with the mesocircuit model and comparable to a tendency for the more anterior prefrontal cortical regions to demonstrate reduced blood flow under anesthesia, sleep, and even early awakening sleep inertia (34,35). Collectively, these findings support a mechanistic link between the key role of the posterior medial complex in outcomes of DOCs (36), restoration of normal resting metabolic activity (33), and restoration of anterior forebrain mesocircuit function via activity of the c-TH (13,14).…”
Section: Fronto-parietal Cortical Metabolic Down-regulation In the Sesupporting
confidence: 74%
“…3); this finding is also consistent with the mesocircuit model and comparable to a tendency for the more anterior prefrontal cortical regions to demonstrate reduced blood flow under anesthesia, sleep, and even early awakening sleep inertia (34,35). Collectively, these findings support a mechanistic link between the key role of the posterior medial complex in outcomes of DOCs (36), restoration of normal resting metabolic activity (33), and restoration of anterior forebrain mesocircuit function via activity of the c-TH (13,14).…”
Section: Fronto-parietal Cortical Metabolic Down-regulation In the Sesupporting
confidence: 74%
“…95 The DMN was shown to be absent in brain death, 96 but still partially preserved in VS, [97][98][99] probably reflecting residual structural connectivity. 93 At the group level, resting-state network activity revealed reduced interhemispheric connectivity 100 and correlated with levels of consciousness in patients with DOC ( Figure 2). 97 At the single-patient level, however, it fails to reliably distinguish VS from MCS, and contamination by motion or other artefacts can impede the identification of true neuronal activity.…”
Section: Functional Mrimentioning
confidence: 99%
“…91,92 Recording of spontaneous fluctuations in BOLD fMRI activity under unstimulated conditions has identified various functional networks, some of which are thought to represent conscious cognitive activity. 71,93,94 The best-studied network is the default mode network (DMN) encompassing the posterior and anterior cortical midline structures, which are considered to be involved in stimulus-independent thought, mind-wandering and self-consciousness. 95 The DMN was shown to be absent in brain death, 96 but still partially preserved in VS, [97][98][99] probably reflecting residual structural connectivity.…”
Section: Functional Mrimentioning
confidence: 99%
“…Studies based on neuroimaging and electroencephalography have found evidence to support the integrated information theory. This theory states that consciousness depends on the brain's capacity to sustain complex patterns of internal communication [39,40]. Hence, if we are able to measure communication between different brain areas, this may be an indication of the degree of consciousness.…”
Section: Recent Advances Changing Our View Of Palliative Sedationmentioning
confidence: 99%